2011
DOI: 10.2147/opth.s22019
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of economic efficiencies in clinical retina practice: activity-based cost analysis and modeling to determine impacts of changes in patient management

Abstract: BackgroundThe purpose of this study is to report the use of activity-based cost analysis to identify areas of practice efficiencies and inefficiencies within a large academic retinal center and a small single-specialty group. This analysis establishes a framework for evaluating rapidly shifting clinical practices (anti-vascular endothelial growth factor therapy, microincisional vitrectomy surgery) and incorporating changing reimbursements for care delivery (intravitreal injections, optical coherence tomography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…1 We found that the small group practice outperformed the academic medical center on nearly all markers of efficiency.…”
mentioning
confidence: 76%
“…1 We found that the small group practice outperformed the academic medical center on nearly all markers of efficiency.…”
mentioning
confidence: 76%
“…Historically, eye examinations in hospital eye clinics have been fragmented, inefficient, and costly. 4 6 , 8 The binocular OCT prototype combines many routine tests into one single instrument, with the aim of improving the speed and efficiency of patient flow, in addition to providing reproducible and quantitative data for several aspects of the eye examination. Designed as an automated, patient-operated device, usability testing is indispensable to predict the likelihood of future successful implementation in eye clinics.…”
Section: Discussionmentioning
confidence: 99%
“…3 Although reasonably quick and safe to perform, the costs involved with operating OCT devices are not trivial. 4 , 5 Commercial devices are expensive to purchase, and the costs of associated labor to capture the OCT scans are even greater. 4 The requirement for OCT and other imaging also places increasing demand on ophthalmology clinics, with fragmented patient pathways and often extended waiting times.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For wet AMD, OCT is frequently preferred to FFA in assessing the efficacy of therapeutic strategies due to its non-invasiveness. OCT is also used as a screening tool to exclude the presence of wet AMD [40,41]. Combining SD-OCT with FAF or NIA images, enables the correlation of the topographic distribution of GA with cross sectional alterations in real-time [42,43].…”
Section: Optical Coherence Tomographymentioning
confidence: 99%